Repercussões da formação de professores (as) no contexto de uma creche do Programa Proinfância no município de São José de Ribamar - SILVA, Nelcir Francisca da (2020)
The research, the origin of this Dissertation, aimed to understand the contributions of teacher training to the work they do in crèches and pre-schools built on the model of the National Education Program Restructuring and Acquisition of Equipment for the Public School Network of Child Education (Proinfância). The empirical field of this research is a kindergarten B, in the municipality of São José de Ribamar - MA. This choice was made because it is a daycare considered a standard for the education of children aged zero to five according to parameters of that Program, regarding the physical space and the repercussions related educational activities. It is understood that the training of teachers, both initial and continuing, as an essential condition for the development of pedagogical work, mainly with young children, this investigation was guided by the following questions: theoretical and practical knowledge acquired in the training of teachers have contributed to develop work with children in this age group in a daycare organized under the Proinfância model? The municipality has developed public policies for the continuing training of teachers of education childish? In addition to that general objective, specific objectives were proposed understand if and how the training of teachers has been support for challenges, experiences and expectations present in your professional routine; analyze the extent to which guidelines and conceptions related to Education legislation Children have been implemented in the context of a daycare structured according to the standard of Proinfância, as well as the possible actions undertaken by the municipality for the training and improvement of teachers who work in the Child education. The qualitative exploratory approach in the form of research This field being subsidized by bibliographic research and document analysis, is the that best suited the proposed objectives. As a result, they show the essential need for public policies geared towards training so that the teachers develop a work of excellence not only in the daycare centers of Proinfância, as well as for all child education in the municipality.